2018
DOI: 10.1111/joic.12542
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary focal nitroglycerin injection through drilled balloon is very effective in the resolution of coronary spasm versus into proximal coronary artery: A prospective randomized comparison study

Abstract: The local administration of NTG to a spasming area through a perforated balloon is more effective and safer than the proximal administration of NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…800µg NTG diluted in 10 cc isotonic NaCl solution was infused through the catheter after vessel recanalization in the study. This dose of GTN is close however slightly higher than previous coronary artery research in which 200-500ug GTN was given through a catheter (19)(20)(21)(22)(23). Our study suggests that 800µg is safe for post recanalization cerebral administration.…”
Section: Discussionmentioning
confidence: 42%
“…800µg NTG diluted in 10 cc isotonic NaCl solution was infused through the catheter after vessel recanalization in the study. This dose of GTN is close however slightly higher than previous coronary artery research in which 200-500ug GTN was given through a catheter (19)(20)(21)(22)(23). Our study suggests that 800µg is safe for post recanalization cerebral administration.…”
Section: Discussionmentioning
confidence: 42%
“…Notably, rapid administration of intracoronary nitrate following provocative testing has resulted in no reported procedure-related deaths[ 13 ]. Furthermore, recent studies have demonstrated more efficacy and safety with local administration of nitroglycerin to spasming areas through a perforated balloon rather than proximal administration of nitroglycerin, which may further reduce minor risks associated with provocative testing[ 33 ] . The impact of local nitroglycerin administration on a spasming area of coronary artery can be visualized in Figures 1 and 2 .…”
Section: Diagnosticsmentioning
confidence: 99%
“…Achievement of NTG administration was determined by the occurrence of at least 20 mmHG drops in arterial blood pressure. the other hand, coronary vasospasm is involved in the etiopathogenesis of ACS and may cause a lower estimation of preferred stent size in where the stent will be placed as well as increases myocardial ischemia [6]. Thus, intracoronary NTG is frequently used during coronary angiography to identify reversible coronary vasospasm.…”
Section: Introductionmentioning
confidence: 99%